2017
DOI: 10.9758/cpn.2017.15.3.222
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the SNAP-25 Polymorphism and Omission Errors in Korean Children with Attention Deficit Hyperactivity Disorder

Abstract: ObjectiveThis study aimed to investigate the association between the synaptosomal-associated protein 25 kDa (SNAP-25) genotype and performance on the continuous performance test (CPT) in Korean children with attention-deficit/hyperactivity disorder (ADHD).MethodsEighty-seven children with ADHD (mean age, 9.23±1.99 years) participated in this study. Omission errors, commission errors, reaction time, and reaction time variability on the CPT were analyzed. The single-nucleotide polymorphism (SNP) rs3746544 (1065 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Of the 45 children with ADHD, 4 children withdrew from the study due to intolerable adverse reactions (nausea, vomiting, and dizziness) to MPH, and 3 children missed follow-up for personal reasons; finally, a total of 38 children (age range, 6.76–12.08 years; mean age, 8.72 ± 1.16 years) completed the follow-up study. Due to the small number of participants with the SNAP-25 G/G genotype, based on the presence of the rare G allele, the sample was divided into two groups: T/T genotype (27 children) and G allele carriers (T/G + G/G, 11 children) (Kim et al, 2017 ). The number of participants required for adequate statistical power was based on previous studies that investigated drug effects in ADHD patients using fNIRS (Monden et al, 2012a ; Matsuura et al, 2014 ; Sanefuji et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Of the 45 children with ADHD, 4 children withdrew from the study due to intolerable adverse reactions (nausea, vomiting, and dizziness) to MPH, and 3 children missed follow-up for personal reasons; finally, a total of 38 children (age range, 6.76–12.08 years; mean age, 8.72 ± 1.16 years) completed the follow-up study. Due to the small number of participants with the SNAP-25 G/G genotype, based on the presence of the rare G allele, the sample was divided into two groups: T/T genotype (27 children) and G allele carriers (T/G + G/G, 11 children) (Kim et al, 2017 ). The number of participants required for adequate statistical power was based on previous studies that investigated drug effects in ADHD patients using fNIRS (Monden et al, 2012a ; Matsuura et al, 2014 ; Sanefuji et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…SNAP25 is an essential component of the soluble N-ethylmaleimidesensitive factor attachment protein receptor (SNARE) complex, which is involved in the exocytotic release of neurotransmitters during synaptic transmission (Antonucci et al, 2016). More recently, SNAP25 variants were reported to be associated with working memory (Wang et al, 2018) and neuropsychological performance in individuals with ADHD (Kim et al, 2017) Evidence also suggests that SNAP25 is differentially expressed in the prefrontal cortex of animal models of ADHD and of children with ADHD when compared to controls (Li et al, 2009). Having previously identified that marker SNAP25-rs362990 conferred susceptibility to ADHD (Puentes-Rozo et al, 2019) and finding that this same variant is associated with the severity of inattention and impulsivity symptoms (Table 2) expands our understating of the role of SNAP25 in ADHD etiology.…”
Section: Discussionmentioning
confidence: 99%
“…Undifferentiated PC12 cells were exposed to B­[a]P for 24 h, revealing decreased expression of SNAP-25, a protein involved in neurotransmitter release. This decrease in SNAP-25 levels leads to insufficient dopamine (DA) release in the brain, resulting in attention-deficit/hyperactivity disorder . PC12 cells are also valuable for studying oxidative stress induced by pollutants, elucidating mechanisms involving ROS generation, glutathione oxidation, cytochrome c release, and the induction of apoptosis …”
Section: Immortalized Cell Linesmentioning
confidence: 99%